THE HR DIAGRAMS OF YOUNG CLUSTERS AND THE FORMATION OF PLANETARY SYSTEMS - POVEDA, ARCADIO (UNAM, Observatorio Astronómico Nacional, CD MEXICO, DF, MEX, 1968)
The existence of T Tauri and flare stars located below the main sequence in some young clusters pose a difficult problem of interpretation for gravitational contraction within conventional stellar theory. We introduce the hypotheses that when solar type p
BOL OBS TONAN TACUB
Keywords: DIAGRAMs, YOUNG CLUSTERS, FORMATION, PLANETARY SYSTEMS; ASTRONOMIA Y ASTROFISICA; ASTRONOMIA OPTICA; ATMOSFERA PLANETARIA